Clinical outcomes of chimeric antigen receptor T-cell therapy following autologous hematopoietic stem cell transplantation in 38 patients with refractory/relapsed primary or secondary central nervous system lymphoma - Jiaying Wu; Wanying Liu; Yang Cao; Yang Yang; Zhen Shang; Mi Zhou; Yicheng Zhang; Fankai Meng; Xiaojian Zhu; Yi Xiao (Cancer Immunology, Immunotherapy)
Abstract Background Several reports have indicated that chimeric antigen receptor (CAR) T-cell therapy following autologous hematopoietic stem cell transplantation (ASCT) is a promising strategy for refractory/relapsed (r/r) central nervous system lymphoma (CNSL), but the number of reported cases is limited. Methods The cohort in this retrospective study consisted of 38 patients with r/r CNSL who received CAR T-cell therapy following ASCT at our center between January 2019 and April 2024. Group comparisons of continuous variables were tested using the unpaired Student’s t-test or the Mann–Whitney U-test, while categorical variables were analyzed using Fisher's exact test. The Kaplan–Meier method was employed to estimate survival curves, and group comparisons were performed using the log-rank test. Results The cohort comprised 38 patients with r/r CNSL, all of whom had active CNS involvement. After therapy, the best overall response rate (ORR) of all patients was 78.9%. Subgroup analysis found that a lower ORR was observed in patients with lactate dehydrogenase levels above the upper limit of normal (60.0% vs. 91.3%, P = 0.039). With a median follow-up of 37.5 months, the estimated 1-year overall survival (OS) and progression-free survival (PFS) rates were 72.8% and 57.4%, respectively. The risk factors associated with PFS was no response to current therapy (adjusted hazard ratio: 22.87, P < 0.001). The incidence rates of severe cytokine release syndrome and immune effector cell-associated neurotoxicity syndrome were both 13.2%. Among the 25 patients with secondary CNSL (SCNSL), the best ORRs were 91.7% for those with CNS lesions only and 61.5% for those with CNS and systemic lesions (P = 0.160), while the estimated 1-year PFS rates were 83.3% and 38.5%, respectively (P = 0.030). Conclusions CAR T-cell therapy following ASCT shows promising efficacy for r/r CNSL patients. Besides, SCNSL patients with CNS and systemic lesions have inferior treatment efficacy compared to those with CNS lesions only.